Unearthing the hidden treasure: Economic viability of teasel gourd(Momordica dioica) enterprise in Uttara Kannada, India - RAJU R; Ashoka N; Hongal, Shivanand; Harshavardhan M; Ravi Y; Tirakannanavar, Shantappa; Venkateshalu; Ganeshgouda I Patil (Journal of Horticultural Sciences, 2024)
Uttara Kannada district, nestled in the Western Ghats of Karnataka, harbours a treasure trove of underutilized crops thriving in their natural wild habitat. Teasel gourd is traditionally grown by a few farmers, primarily for personal consumption or sporadically collected from the wild for sale. This crop has remained largely unexplored in terms of its economic viability. This study endeavours to shed light on its economics, based on primary data collected from 30 randomly selected farmers in Uttara Kannada, India during the year 2023. The findings revealed that the teasel gourd garden establishment requires an investment of up to ₹5,97,668 per hectare. The subsequent maintenance costs ranged from ₹2,94,460 in the first year to ₹3,65,830 by the fifth year. The net returns from teasel gourd farming are strikingly promising, fluctuating between ₹16,49,795 in the first year to ₹14,13,020 by the fifth year, and the higher B:C ratio figures out the crop’s potential to significantly boost the income of farmers. This study underscores the need for capacity-building programs aimed at popularizing teasel gourd cultivation among farmers in Uttara Kannada, India. By tapping into this underutilized crop’s economic potential, one can not only enhance the livelihoods of local farmers but also contribute to the realization of the Government of India’s vision of vocal-for-local. Hence, teasel gourd farming will be the key to unlocking prosperity in Uttara Kannada’s agricultural landscape.